Mental Health in the Workplace: what Librarians in Croatia Think about It? - Antonija Filipeti; Marta Romac; Adrijana Al-Nidawi (Bosniaca)
Goal: Training Centre for Continuing Education of Librarians in Croatia (CSSU), which has conducted programs of professional development for librarians and information specialists since 2002, as a part of the National and University Library in Zagreb, carried out trainings on mental health in the workplace in 2022, which received great interest from the participants. The aim of this paper is to examine the attitudes of participants in educational programs and to present feedback on satisfaction and interest in additional educational content. Another goal is to explore the current awareness of the importance of mental health in the workplace within the Croatian library community. Approach/methodology: The research utilized three data sources: the archival documentation of CSSU from 2022 for the interpretation of numerical indicators of program implementation, an evaluation questionnaire on satisfaction with professional development, and an orientation questionnaire on mental health in the workplace, which were distributed to participants electronically after the educational sessions. Results: The results indicate a high level of participant satisfaction with the instructor, educational content, and presentation materials, as well as a willingness to recommend the training to colleagues in the field. Participants additionally suggest a deeper insight into the topic and express a desire for further training. Limitations: The percentage of completed questionnaires on mental health in the workplace is lower, which can be considered a limitation in interpreting the librarians’ attitudes. Originality/Value: The originality of this work arises from its focus on the unique needs and challenges of the library work environment, where mental health has traditionally not received significant attention. By collecting feedback through questionnaires, the study provides insights into the existing level of awareness regarding mental health and the need for further education. Social Significance: By raising awareness of the importance of mental health in the workplace, this study contributes to the creation of a supportive and informed work culture, which in the long term may lead to a reduction in professional stress and an enhancement of the quality of library services. The findings can serve as a starting point for other sectors in recognizing the importance of mental health, especially in those that involve public services and working with people.